(untitled) (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
The evolution of the internet into Web3 has redefined digital ownership, governance, and privacy. Unlike traditional identity management systems that rely on centralized authorities, Decentralized Identity Management (DIM) utilizes blockchain technology to empower individuals with control over their personal data. This research explores the role of decentralized identity in enhancing user privacy, security, and trust in Web3 environments. The study analyzes the integration of blockchain-based identity solutions such as Self-Sovereign Identity (SSI), Decentralized Identifiers (DIDs), and Verifiable Credentials (VCs) within decentralized applications (dApps) and digital ecosystems. Using a mixed-method approach combining technical analysis and user-based surveys, findings reveal that decentralized identity significantly mitigates data breaches, improves authentication transparency, and fosters trustless digital transactions. The study also examines interoperability challenges, scalability constraints, and regulatory implications to provide a comprehensive framework for sustainable and user-centric identity governance in Web3